Importance of cooperation between the Republics of China-Taiwan and Paraguay (Legal journal - Research in Legal and Social Sciences, 2024)
It is necessary to highlight the significance of the Paraguayan-Chinese Association for Friendship and Cooperation, as it has played a fundamental role in fostering and consolidating the relationship between the Republic of China (Taiwan) and the Republic of Paraguay, both economically and politically. This association stands as a guarantor of this brotherhood, facing the ‘Sword of Damocles’ posed by Red China, which seeks to entice the political establishment with continuous incentives and promises, aiming to isolate Taiwan internationally and orchestrate a historical rupture that could have negative consequences for Paraguay. To this end, a qualitative, non-experimental, and documentary research approach was employed through bibliographic review and document analysis. The study concludes by underscoring that this association is exemplary, as it embodies the duties of the homeland and the freedom of peoples, carrying out an extensive and transversal effort to maintain the Taipei-Asunción connection. It also functions as an agent performing quasi-diplomatic activities due to the caliber of its members, serving both governments in office as advisors. Thus, it is argued that this association stands as an international benchmark for partnership and serves as a model for other nations to follow.
Keywords: Paraguay; China-Taiwan; cooperation; humanitarian aid; agreement